Korelasi antara Skor Osteoporosis Self Assessment Tool for Asians dengan Skor FRAX® pada Wanita Usia Lanjut - Ma'ruf, Muhammad; Yuwana, Sugeng (Universitas Ahmad Dahlan, 2019)
Background: Osteoporosis and osteoporotic fractures are an important public health concern in the elderly, especially in post-menopausal women. Screening for osteoporosis might help to detect those at risk for fractures to be promptly managed. WHO has developed a tool to screen risk for osteoporosis, i.e. the Osteoporosis Self-assessment Tool (OST) that has also been validated for Asians (OSTA). WHO has also developed FRAX® to predict 10-years risk of hip fracture or other osteoporotic a fracture. Method: This study was intended to assess the correlation between OSTA and FRAX®. This cross-sectional study was performed in October-December 2013 in all public health centers (Puskesmas) in Yogyakarta, Indonesia. We invited all women aged 56 years or above visiting the outpatient clinic of the Puskesmas during the study period. Overall, 540 elderly women completed the anthropometric measurements and questionnaires of FRAX®. Results: OSTA scores showed that more than 40% were at high risk for osteoporosis. This study observed high and significant correlations between OSTA and FRAX® for hip fracture, i.e. Spearman correlation of 0,914; p<0,001 and for other osteoporotic fractures, i.e. Spearman correlation of 0,769; p<0,001. Conclusion: We concluded that OSTA and FRAX® were highly correlated and both can be used to screen women for osteoporosis and risk for fractures, respectively.